Hemodialysis Induces an Acute Decline in Cerebral Blood Flow in Elderly Patients - Polinder-Bos, Harmke A. (J Am Soc Nephrol, 2018)
The initiation of hemodialysis is associated with an accelerated decline of cognitive function and an increased incidence of cerebrovascular accidents and white matter lesions. Investigators have hypothesized that the repetitive circulatory stress of hemodialysis induces ischemic cerebral injury, but the mechanism is unclear. We studied the acute effect of conventional hemodialysis on cerebral blood flow (CBF), measured by [(15)O]H(2)O positron emission tomography–computed tomography (PET-CT). During a single hemodialysis session, three [(15)O]H(2)O PET-CT scans were performed: before, early after the start of, and at the end of hemodialysis. We used linear mixed models to study global and regional CBF change during hemodialysis. Twelve patients aged ≥65 years (five women, seven men), with a median dialysis vintage of 46 months, completed the study. Mean (±SD) arterial BP declined from 101±11 mm Hg before hemodialysis to 93±17 mm Hg at the end of hemodialysis. From before the start to the end of hemodialysis, global CBF declined significantly by 10%±15%, from a mean of 34.5 to 30.5 ml/100g per minute (difference, −4.1 ml/100 g per minute; 95% confidence interval, −7.3 to −0.9 ml/100 g per minute; P=0.03). CBF decline (20%) was symptomatic in one patient. Regional CBF declined in all volumes of interest, including the frontal, parietal, temporal, and occipital lobes; cerebellum; and thalamus. Higher tympanic temperature, ultrafiltration volume, ultrafiltration rate, and pH significantly associated with lower CBF. Thus, conventional hemodialysis induces a significant reduction in global and regional CBF in elderly patients. Repetitive intradialytic decreases in CBF may be one mechanism by which hemodialysis induces cerebral ischemic injury.